The Impact of Flexibility in Human Resource Management on Employee Performance - Njoud AlJohani (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
The current study aimed to examine the impact of human resource flexibility on improving employee performance in small and medium-sized enterprises (SMEs) in Saudi Arabia. The study adopted a descriptive-analytical approach, and fieldwork was conducted on a sample of 123 administrative employees, supervisors, and managers working in SMEs. A structured questionnaire was used as the main tool for data collection, consisting of three main dimensions: HR flexibility, organizational commitment, and employee performance. The study revealed several key findings, most notably that human resource flexibility positively affects employee performance by enhancing their ability to adapt to changing work conditions and improve work quality and productivity. Furthermore, flexibility was found to play a crucial role in increasing employee commitment and job satisfaction, which in turn boosts overall performance. The study recommended the importance of adopting flexible HR practices in SMEs to foster a more dynamic and responsive workforce. Additionally, it emphasized the need for continuous employee development and training to further enhance performance and adaptability in changing work environments.